PENERAPAN BALANCED SCORECARD DALAM PENILAIAN KINERJA PENGELOLA PAJAK BUMI DAN BANGUNAN KOTA PAREPARE (STUDI KASUS PADA KELURAHAN WATANG SOREANG) - Arham, Arham; Syukri, Fitriyani; Astuti, Dwi Rias (Cateris Paribus Journal, 2022)
Performance measurement is important for public organizations, in the context of good governance. This study aims to determine the application of the Balanced Scorecard in assessing the performance of the Land and Building Tax Managers in the Parepare City. Data collection techniques used in this study are questionnaires, observation, and documentation. The subjects in this study were the research sample, namely PBB P2 managers and taxpayers in Watang Soreang Village. This study used quantitative analysis. The results of the study concluded that the application of the Balanced Scorecard in assessing the performance of Land and Building Tax Managers in Parepare City, namely by applying 4 (four) perspectives : financial perspective; customer perspective (taxpayer; internal business perspective); and learning and growth perspective